The Relationship between Status at Presentation and Outcomes among Pregnant Women with COVID-19 - London, Viktoriya; McLaren, Rodney, Jr.; Atallah, Fouad; Cepeda, Catherine; McCalla, Sandra; Fisher, Nelli; Stein, Janet L.; Haberman, Shoshana; Minkoff, Howard (American Journal of Perinatology, 2020)
Objective This study was aimed to compare maternal and pregnancy outcomes of symptomatic and asymptomatic pregnant women with novel coronavirus disease 2019 (COVID-19).Study Design This is a retrospective cohort study of pregnant women with COVID-19. Pregnant women were divided into two groups based on status at admission, symptomatic or asymptomatic. All testing was done by nasopharyngeal swab using polymerase chain reaction (PCR) for severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2). Initially, nasopharyngeal testing was performed only on women with a positive screen (symptoms or exposure) but subsequently, testing was universally performed on all women admitted to labor and delivery. Chi-square and Wilcoxon's rank-sum tests were used to compare outcomes between groups.Results Eighty-one patients were tested because of a positive screen (symptoms [n = 60] or exposure only [n = 21]) and 75 patients were universally tested (all asymptomatic). In total, there were 46 symptomatic women and 22 asymptomatic women (tested based on exposure only [n = 12] or as part of universal screening [n = 10]) with confirmed COVID-19. Of symptomatic women (n = 46), 27.3% had preterm delivery and 26.1% needed respiratory support while none of the asymptomatic women (n = 22) had preterm delivery or need of respiratory support (p = 0.007 and 0.01, respectively).Conclusion Pregnant women who presented with COVID19-related symptoms and subsequently tested positive for COVID-19 have a higher rate of preterm delivery and need for respiratory support than asymptomatic pregnant women. It is important to be particularly rigorous in caring for COVID-19 infected pregnant women who present with symptoms.Key Points
Keywords: COVID-19; lymphopenia; preterm delivery; SARS-CoV-2; vertical transmission